THE FACTORS AFFECTING FARMERS' INCOME AND WELFARE IN KLAMBIR V KEBUN VILLAGE, DELI SERDANG REGENCY - Lubis, Rizal P.; Abdiyanto, Abdiyanto; Sabilayana, Sabilayana (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study investigates the factors affecting farmers' income and welfare in  Klambir V Kebun Village, Deli Serdang Regency, with a focus on how land area, capital access, and market pricing influence agricultural productivity.  Agriculture plays a crucial role in Indonesia's economy, providing livelihoods for many, particularly in rural communities. The research highlights that  larger land areas enhance production capacity, which directly correlates with increased income levels. Access to financial resources is essential for farmers to invest in necessary agricultural inputs, while favorable market prices significantly impact their earnings. The role of local institutions, such as Village Economic Enterprises (BUMDes), is also emphasized as vital for supporting farmers. The study employs a descriptive qualitative methodology, utilizing field data and literature to analyze the interplay of these factors. Findings underscore the necessity for targeted interventions, including training programs, access to credit, and infrastructure improvements, to bolster farmers' economic conditions and promote sustainable agricultural practices. Overall, this research contributes to understanding and enhancing the welfare of farmers in Klambir V Kebun Village, ensuring their economic sustainability and improved quality of life.